Evaluation of oxidative stress among coronary diabetics patients - Dandana, A.; Ferchichi, S.; Addad, et al., F. (Acta Biomedica Atenei Parmensis, 2012)
Abstract. Objectives: Determination of the superoxide dismutase (SOD), glutathione peroxidase (GPX) and the total antioxidant status (TAS) and evaluation of inflammation by the use of high sensitivity C reactive protein (hs-CRP) among Tunisian coronary diabetic patients. Materials and methods: We measured the erythrocyte GPX activity and the plasmatic TAS concentration by colorimetric methods, the apolipoproteins [ApoA1, ApoB], hs-CRP and the fibrinogen by immunonephelometry assays. Results: TAS and GPX were significantly decreased among patients compared to the controls [TAS: 1,14 ± 0,28 mmol/l vs 1,55 ± 0,35 mmol/l, GPX: 59,32 ± 10,72 U/gHb vs 149,19 ± 30,95 U/gHb]. For the coronary diabetic patients, the TAS is correlated positively with hs-CRP [r= 0,01, p<10-3]. Pearson’s correlation shows a significantly positive correlation between GPX and TAS among all patients. Conclusions: Determination of antioxidative defense markers contributes to understanding the effect of stress oxidative on the development, prevention and therapy of cardiovascular disease.